Dataset on non-carcinogenic risk via nitrate and nitrite in the groundwater of Divandarreh County, Kurdistan province, Iran: A potential concern for drinking - Abotaleb bay; Shakir Ali; Mansoureh Ghezelsofla; Hassan Keramati; Bigard Moradi; Yadolah Fakhri (Data in Brief, 2018)
The presence of elevated nitrate (NO3-) and nitrite (NO2-) concentration in drinking water higher than the standard limits could endanger the health of consumers. For this data article, concentration of NO3- and NO2- was measured in 118 samples collected from 59 active rural wells in Divandarreh County and the non-carcinogenic risk in the adults and children was estimated by Monte Carlo simulation (MCS). The obtained data showed that the average concentration of NO3- and NO2- was ranges from 31.37 ± 18.87 mg/L and 1.45 ± 0.90 mg/L respectively. Based on acquired data, NO3- concentrations were 37 times higher than NO2- with significant p value of < 0.05. The average concentration of NO3- and NO2- was lower than the national standard with p value < 0.05. However, the concentration of NO3- and NO2- in 23.7% and 13.5% of wells was higher than the national standard of Iran. Total target hazard quotient (TTHQ) in the adults and children was 1.78 and 1.54, respectively. Although, the average concentration of NO3- and NO2- in drinking water was lower than the national standard limits, but the non-carcinogenic risk assessment showed that the children and adults are at a significant risk via nitrate and nitrite in the rural Divandarreh County (TTHQ > 1). Keywords: Nitrate, Nitrite, Groundwater contamination, Risk assessment, Rural Iran, Divandarreh County